(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article discusses the roles of Information and communication technology (ICT) in education. Information communication technologies at present are influencing every aspect of human life. ICT has the potential to enhance participation in educational activities for students in learning process.